ANALISIS PENGARUH HARGA, PROMOSI, PELAYANAN, DAN KUALITAS PRODUK ONLINE TERHADAP KEPUASAN KONSUMEN ONLINE SECARA SYARIAH - Deery Anzar Susanti (Journal Analytica Islamica, 2016)
This study aims to analyze how closely the relationship and influence between price, promotion, service, and quality of products online to customer satisfaction online. The samples using non-probability sampling techniques 100 respondents through accidental sampling method. This study uses a questionnaire measuring instrument has been tested stationary data so it can be used to measure the variables of the study.The results showed that there was significant effect between variables either partially or simultaneously. The results of the calculations also show that online consumer satisfaction is seen as one of the dimensions of market performance, increase customer satisfaction tends to lead to long-term sales growth. In addition to providing some benefits, it also provides a good basis for the purchase and creation of customer loyalty, as well as forming a recommendation by word of mouth that is profitable for the company.